Evaluating atherosclerosis prevalence via coronary calcium in executives with normal LDL levels in the US: a cohort study–the clear protocol - Ivana Croghan; Ann Vincent; Ryan T Hurt; Basem M Ratrout; Basant E Katamesh; Sara Bonnes; Jayanth Adusumalli; Donna K Lawson; Darrell Schroeder; Christina D VerNess (BMJ Open)
Introduction The coronary artery calcium (CAC) scan serves as a crucial tool in assessing the risk of coronary atherosclerosis in patients with hyperlipidaemia, particularly when there is ambiguity surrounding pharmacotherapy decisions. In addition to CAC, advanced glycation end products (AGEs), glycated proteins and lipids involved in ageing are emerging as markers for atherosclerosis. However, the relationship between AGEs score and CAC scores has not been evaluated to date. Our primary objective is to evaluate abnormal CAC scores in patients with low and borderline ASCVD risk and normal low-density lipoprotein cholesterol (LDL-C) levels ≤100 mg/dL. The secondary objective is to explore potential associations between CAC and AGEs scores.Methods and analysis We will retrospectively review health records of adult patients seen at the General Internal Medicine Executive Health Program (Mayo Clinic; Rochester, Minnesota) between 1 September 2023 and 31 March 2024, where all patients were offered the option of a baseline CAC scan. For our primary aim, we will determine the percentage of patients with low and borderline 10-year Atherosclerotic Cardiovascular Disease (ASCVD) risk, not receiving pharmacotherapy for hyperlipidaemia, who have LDL-C levels ≤100 mg/dL and have an abnormal CAC score. For our secondary aim, we will examine potential associations between CAC and AGEs scores.Ethics and dissemination This study was determined to be exempt from institutional review board approval (ID 24–0 03 921; 45 CFR 46.104d, category/subcategory 4(iii)) at the Mayo Clinic, Rochester. The findings of this study will be published in a peer-reviewed journal.